If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 + 15 = 8 Reorder the terms: -3 + 15 + 6x = 8 Combine like terms: -3 + 15 = 12 12 + 6x = 8 Solving 12 + 6x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 8 + -12 6x = 8 + -12 Combine like terms: 8 + -12 = -4 6x = -4 Divide each side by '6'. x = -0.6666666667 Simplifying x = -0.6666666667
| 2(x-1)=8+2x | | -37=3v+2(v+4) | | 3/2=n | | 12x+2y=80 | | -12+5x=38 | | (4+3i)(5+5i)=equation | | 4x+4x+7x=105 | | 35=7u+5(u-5) | | 3+5x=2345 | | 2x-21=15-7x | | x-5=8x+16 | | -16.5p+2.46=-16.7p | | 210+0.15x=372 | | 2x-2(-6+14)=42 | | 7x-4=2x-40 | | x*15=x+1*10 | | -5.69+6j=12.4j+10.31 | | -3z+5=8 | | x/2-7=-12 | | -19v=-4.47-19.3v | | 8y+12=3y+6 | | 8y-12=3y+6 | | 4(6x+1)+2x=2 | | -3/4x=3/5 | | 8s+3=11 | | solveV=lwh | | 21/2m=133/4 | | 4x-7+86=9x+4 | | 6j-5=4j-7 | | 2(x-6)=6(x+4) | | 6j+5=4j-7 | | -3(2x-4)=4(1.5x-3) |